Persepsi Siswi Perempuan terhadap Perilaku Seks Bebas - Elin Eria Putri; Dosi Juliawati; Hengki Yandri (Indonesian Journal of Counseling and Development, 2021)
Today's teenage promiscuity is so concerning that some have casual sex. So the purpose of this study is to uncover the perception of female students of free sex behavior. This research method is quantitatively descriptive with the research population of all students of State Junior High School 24 Kerinci with the research subjects of all female students in class VII and VIII which amounted to 39 people. The data was revealed using the Free Sex Behavior scale, then processed descriptively. The results of this study revealed that female students perceive free sex behavior is a bad thing to do meaning that the average student has a perception with a good category. For that, it is recommended to the next researcher to research with a wider scale of research subjects